DOES INFILTRATION OF LOCAL ANESTHESIA IN THE POSTERIOR CAPSULE REDUCES PAIN IN TOTAL KNEE REPLACEMENT WHEN COMPARED WITH PLACEBO - SIDDIQ , MZ; SARWAR, S; SHAHZADI, I; RAZZAQUE , MA; SHAFIQ , M; ATIF , M (Biological and Clinical Sciences Research Journal, 2023)
The current analysis aimed to determine the mean pain score after injecting long-acting local anesthesia in the posterior capsule after a total knee replacement by comparing it with the placebo group. This prospective cohort study was conducted in the orthopedic department of Aziz Bhatti shaheed teaching hospital Gujrat from 1st June to 31st December 2022. The mean pain score was assessed at the end of 24 hours after postoperative surgery and measured by a visual analog scale (VAS = 0-10) where 0 was taken as no pain and 10 as worst pain. We divided cases into groups A and B. Group A was given a drug, and Group B was given normal saline. The knee pain score was calculated at the end of 24 hours postoperatively. Out of 222 patients, (47.30%) were male and 117(52.70%) were female, with ages ranging from 40 to 70 years; in group A, the mean age was 58.29±6.84 years and 58.39 ±7.33 years in group B. The mean BMI was 30.55±2.46 kg/m2. In group A, 52 (46.85%) patients had DM, while 49 (44.14%) were in group B. The mean pain score in group A was 2.95±0.98 and 4.44±1.13 in group B with p-value =0.0001. Stratification of pain score was performed concerning age, gender BMI and DM. Statistically significant results were found among age and gender. This study concluded that there is less mean pain score after long-acting local anesthesia in posterior knee capsules compared with placebo in total knee replacement.